Atlantic Water Properties, Transport and Heat Loss From Mooring Observations North of Svalbard. Issue 8 (26th August 2022) - Koenig, Zoe; Kalhagen, Kjersti; Kolås, Eivind; Fer, Ilker; Nilsen, Frank; Cottier, Finlo
Abstract: The Atlantic Water inflow to the Arctic Ocean is transformed and modified in the area north of Svalbard, which influences the Arctic Ocean heat and salt budget. Year‐round observations are relatively sparse in this region partially covered by sea ice. We took advantage of one‐year‐long records of ocean currents and hydrography from seven moorings north of Svalbard. The moorings are organized in two arrays separated by 94 km along the path of the Atlantic Water inflow to investigate the properties, transport and heat loss of the Atlantic Water in 2018/2019. The Atlantic Water volume transport varies from 0.5 Sv (1 Sv = 10 6  m 3 s −1 ) in spring to 2 Sv in fall. The first mode of variation of the Atlantic Water inflow temperature is a warm/cold mode with a seasonal cycle. The second mode corresponds to a shorter time scale (6–7 days) variability in the onshore/offshore displacement of the temperature core linked to the mesoscale variability. Heat loss from the Atlantic Water in this region is estimated, for the first time using two mooring arrays and conserving the volume transport. The heat loss varies between 302 W m −2 in winter to 60 W m −2 in spring. The onshore moorings show a westward countercurrent driven by Ekman setup in spring, carrying transformed‐Atlantic Water. The offshore moorings show a bottom‐intensified current that covaries with the wind stress curl. These two mooring arrays allowed for a better comprehension of the structure and transformation of the slope currents north of Svalbard. Plain Language Summary: Atlantic Water enters the Arctic Ocean along two pathways, through the Barents Sea and through Fram Strait west of Svalbard, and is the main heat and salt source for the Arctic Ocean. We use temperature, salinity and current observations from seven lines of oceanic instruments moored to the seafloor and organized in two arrays, deployed in fall 2018 for one year north of Svalbard to analyze the properties and variations of the Atlantic Water inflow and its rate of cooling between the two arrays on its path to the Arctic Ocean. We report a westward flow on the upper slope, carrying diluted Atlantic Water mixed with colder shelf waters. At about 1, 000 m depth a deep‐intensified current carries deep waters. Both currents are influenced by the winds. The heat loss of the Atlantic Water while it travels eastward varies between 302 W m −2 in winter to 60 W m −2 in spring. These new observations from two mooring arrays offer new insight on the structure and variations of the slope currents north of Svalbard, as the circulation pathways and the heat transported by the Atlantic Water influence the seasonal variations of the sea ice and the marine ecosystems. Key Points: The heat loss from the Atlantic Water inflow North of Svalbard varies between 302 W m −2 in winter and 60 W m −2 in spring A surface countercurrent on the upper slope carrying transformed Atlantic Water is modulated by the Atlantic Water inflow and Ekman setup An offshore bottom‐intensified current is detected on the lower slope, partly correlated with the wind stress curl